2010
DOI: 10.1093/jxb/erq028
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxylate rather than ascorbate is an efficient precursor for oxalate biosynthesis in rice

Abstract: Oxalate is widely distributed in the plant kingdom. While excess oxalate in food crops is detrimental to animal and human health, it may play various functional roles in plants, particularly for coping with environmental stresses. Understanding its biosynthetic mechanism in plants, therefore, becomes increasingly important both theoretically and practically. However, it is still a matter of debate as to what precursor and pathway are ultimately used for oxalate biosynthesis in plants. In this study, both physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 60 publications
4
78
0
2
Order By: Relevance
“…DNase I-treated total RNA (2.0 mg) was used for reverse transcription using the M-MLV-RT kit (TAKARA, Japan). RT-PCR and real-time quantitative PCR were performed as previously described 39,40 . Briefly, equal amounts of RT products were used to perform PCR.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…DNase I-treated total RNA (2.0 mg) was used for reverse transcription using the M-MLV-RT kit (TAKARA, Japan). RT-PCR and real-time quantitative PCR were performed as previously described 39,40 . Briefly, equal amounts of RT products were used to perform PCR.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…The glyoxylate cycle occurs in bacteria, fungi and plants, but in very few animals; the notable exception being cnidarians (Kondrashov et al, 2006). In plants, glyoxylate is an efficient precursor for oxalate production (Yu et al, 2010). Oxalate combines readily with calcium to form crystalline calcium oxalate (CaC 2 H 2 O 4 ) deposits.…”
Section: Fig 5 (A)mentioning
confidence: 99%
“…However, the relative contribution of these pathways is controversial. For example, Xu et al 7 observed that oxalate accumulation and regulation are independent of glycolate oxidation in rice, while Yu et al 8 observed that glyoxylate rather than ascorbate are an efficient precursor for oxalate biosynthesis.…”
Section: Production Of Oxalic Acid In Plantsmentioning
confidence: 99%